Penerapan Pembelajaran Ctl (Contextual Teaching And Learning) Untuk Meningkatkan Hasil Belajar Ekonomi Siswa Kelas XII IPS 3 - Masmuria Masmuria (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2018)
This research is a class action research (Action research) Aiming To: Improve Economic Learning Outcomes Through Application of Contextual Teaching and Learning CTL ". In this study researchers used qualitative research methods using descriptive analysis approach. In this research, the location that the researcher chose is the students of class XII IPS 3 SMA Negeri 2 Watampone Bone District. The method used to collect data on the implementation of contextual learning by teachers Economics in SMA 2 Watampone Bone District are: Documentation Methods, Interview Methods, and Observation Methods. This classroom action research procedure consists of 2 cycles. Each cycle is implemented in accordance with the changes to be achieved. Cycle I and cycle II are 5 times each. Teachers are expected to improve the quality of learning by providing a contextual and practical learning experience to students, meaning that learning should be meaningful and provide opportunities to train students into real citizens, so as to be able to deal with daily problems in society later.